2014
DOI: 10.1016/j.jcv.2014.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hepatitis C Virus RNA and antibody detection in dried blood spots and plasma specimens

Abstract: Background Current diagnostic tests for Hepatitis C Virus (HCV) involve phlebotomy and serologic testing for HCV antibodies (anti-HCV) and RNA, which are not always feasible. Dried blood spots (DBS) present a minimally invasive sampling method and are suitable for sample collection, storage and testing. Objectives To assess the utility of DBS in HCV detection, we evaluated the sensitivity and specificity of DBS for anti-HCV and HCV RNA detection compared to plasma specimens. Study design This cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
65
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(73 citation statements)
references
References 22 publications
6
65
2
Order By: Relevance
“…This observation may to some extent be caused by the different starting titers of the samples, resulting in different dilution factors by elution. The results are consistent with other studies, where low DBS sensitivities have been reported, ranging between 70% and 100%, with specificities from 94% to 100%[18,25,26]. In the study by Ross, almost perfect sensitivities and specificities for DBS were observed compared to serum samples; however, DBS were prepared by applying 100 μL of whole blood to generate DBS (Whatman filter paper), a procedure that most likely is not possible with DBS in real-world settings, where we estimated the average amount to be 75 μL.…”
Section: Discussionsupporting
confidence: 93%
“…This observation may to some extent be caused by the different starting titers of the samples, resulting in different dilution factors by elution. The results are consistent with other studies, where low DBS sensitivities have been reported, ranging between 70% and 100%, with specificities from 94% to 100%[18,25,26]. In the study by Ross, almost perfect sensitivities and specificities for DBS were observed compared to serum samples; however, DBS were prepared by applying 100 μL of whole blood to generate DBS (Whatman filter paper), a procedure that most likely is not possible with DBS in real-world settings, where we estimated the average amount to be 75 μL.…”
Section: Discussionsupporting
confidence: 93%
“…Anti‐HCV testing in DBS and saliva demonstrated specificity above 90% in HCV and HIV monoinfected groups, which is similar to previous studies using DBS in chronic HCV cases and studies using the Salivette device in individuals with chronic hepatitis C and HIV‐infected individuals . Although high specificities were observed, assays were less specific in HIV‐infected individuals, as was observed by Visseaux et al [2013] using saliva samples for anti‐HCV testing in an HIV monoinfected group.…”
Section: Discussionsupporting
confidence: 87%
“…29 Some studies have shown that high-risk populations, such as individuals who have received transfusion and sexually at-risk individuals, may present falsely reactive results for anti-HCV detection, which could be the product of cross-reactivity with other infections, such as HIV or HBV. [30][31][32] Anti-HCV testing in DBS and saliva demonstrated specificity above 90% in HCV and HIV monoinfected groups, which is similar to previous studies using DBS in chronic HCV cases 12,[23][24][25]33 and studies using the Salivette device in individuals with chronic hepatitis C and HIV-infected individuals. 19,27,34,26 25 and 75% for saliva samples 21 when the same protocol for serum samples was used.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations